N6-Methyladenosine Modification-Related Genes Express Differentially in Sterile Male Cattle-Yaks - Yuxin Liu; Lili Chen; Hui Jiang; Hongzhuang Wang; Yujiao Zhang; Zhengrong Yuan; Yi Ma (Life)
N6-methyladenosine (m6A), an RNA post-transcriptional modification, plays a crucial role in spermatogenesis. Cattle-yaks are interspecific hybrid offsprings of yak and cattle, and male cattle-yaks are sterile. This study aims to investigate the role of m6A modification in male cattle-yak infertility. Herein, testicular tissues were analyzed via histological observations, immunohistochemical assays, reverse-transcription quantitative polymerase chain reaction, Western blotting, and immunofluorescence assays. The results revealed that male cattle-yaks presented smaller testes (5.933 ± 0.4885 cm vs. 7.150 ± 0.3937 cm), with only single cell layers in seminiferous tubules, and weakened signals of m6A regulators such as METTL14 (methyltransferase-like 14), ALKBH5 (alpha-ketoglutarate-dependent hydroxylase homolog 5), FTO (fat mass and obesity-associated protein), and YTHDF2 (YTH N6-methyladenosine RNA binding protein F2), both at the RNA and protein levels, compared with those of yaks. Altogether, these findings suggest that m6A modification may play a crucial role in male cattle-yak sterility, providing a basis for future studies.